2021
DOI: 10.1186/s42358-021-00229-w
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment using ASCVD risk score in fibromyalgia: a single-centre, retrospective study using “traditional” case control methodology and “novel” machine learning

Abstract: Background In autoimmune inflammatory rheumatological diseases, routine cardiovascular risk assessment is becoming more important. As an increased cardiovascular disease (CVD) risk is recognized in patients with fibromyalgia (FM), a combination of traditional CVD risk assessment tool with Machine Learning (ML) predictive model could help to identify non-traditional CVD risk factors. Methods This study was a retrospective case–control study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, CVD risk was not associated with FMS disease severity and duration. Similarly, our study showed no correlation between disease duration and IMT 41 …”
Section: Discussionsupporting
confidence: 43%
“…However, CVD risk was not associated with FMS disease severity and duration. Similarly, our study showed no correlation between disease duration and IMT 41 …”
Section: Discussionsupporting
confidence: 43%
“…In line with this, a recent study has found that FM patients have a greater glycaemic response to glucose load after one hour and two hours, a larger glucose area under the curve than healthy controls ( 26), and higher mean glycated HbA1c levels (27). Given this prevalence of obesity and glucose intolerance, an Indian study calculated the 10-year and lifetime risk of developing CVD using the atherosclerotic cardiovascular disease (AS-CVD) calculator and found that FM patients aged 40-59 years had increased lifetime CVD risk than controls (OR = 1.56), regardless of FM severity or duration (28). It is therefore important to monitor the metabolic syndrome in FM patients, not least because careful weight control is a forerunner of an improvement in pain levels.…”
Section: Population Characteristicsmentioning
confidence: 99%